Microstructure evolution and elemental diffusion behavior near the interface of Cr2AlC and single crystal superalloy DD5 at elevated temperatures - Li, Jimeng; Jing, Jing; He, Jian; Chen, Hao; Guo, Hongbo (Elsevier Ltd, 2020)
As one of the promising MAX phase materials for high-temperature applications, Cr2AlC is considered as a potential substitution bond coat material in thermal barrier coating systems. In this paper, the microstructure evolution and elemental diffusion behavior near the interface of the diffusion couple composed of Cr2AlC and single crystal superalloy DD5 were investigated at 1100 °C, 1150 °C, and 1200 °C. Elemental interdiffusion between Cr2AlC and DD5 occurs significantly, resulting in the formation of a thick layer of Kirkendall holes after 20 h heat treatment at 1100 °C and higher temperatures. The outward diffusion of Ni into Cr2AlC and the inward diffusion of Al into DD5 alloy causes the formation of β-NiAl matrix embedded with dispersed Cr7C3 phase. Simultaneously, the precipitation of σ-TCP phase and degradation of the γ/γ′ matrix occurs in the alloy. Additionally, TaC, M2C (where M = Ta, W, Cr), and M23C6 (M = Cr, Re, W) compounds are formed near the interface along with the dissolution of σ-TCP phases. It is further found that Al in Cr2AlC exhibits the highest average effective diffusion coefficient among the four dominant diffusing elements. It also displays the lowest diffusion activation energy which is due to its relatively weak Cr-Al and Al-Al bonds.